A taxonomic review of the Chinese species from the genus Ascelosodis Redtenbacher (Coleoptera: Tenebrionidae), with descriptions of three new species - Ren, Guo-Dong; Shi, Ai-Min (Zootaxa, 2006)
Three new species of Ascelosodis Redtenbacher, 1868, A. emarginata, sp. nov., A. punctulata, sp. nov. and A. rugulosa, sp. nov. are described from the Tibetan Plateau, China. A. emarginiventris Koch, 1948, A. everestina Blair, 1923, A. longstaffi Blair, 1923, A. nitida Blair, 1923 A. thibetana Blair, 1923, and A. waltoni Blair, 1923 are originally known in Tibet, and A. haagi Bates, 1879, A. reinigi Koch, 1948, A. schmidi Kaszab, 1965 and A. serripes Redtenbacher, 1868 are reported from China for the first time. A key to all 13 species of Chinese Ascelosodis is given. All Chinese species are distributed in Midwest Tibet (the eastern border is Nang County, 29°06’ N, 93°12’ E).